Theoretical study of the molecular conformations, vibrational frequencies and thermochemistry of the FC(O)OOO(O)CF, FS(O2)OOO(O2)SF and FC(O)OOO(O2)SF trioxides - Badenes, Maria Paula (2013)
The molecular structures, conformational mobilities, harmonic vibrational frequencies and thermochemistry of the FC(O)OOO(O)CF, FS(O2)OOO(O2)SF and FC(O)OOO(O2)SF trioxides were studied by ab initio and density functional methods. The potential energy curves for the internal rotations were calculated using the B3LYP hybrid functional with the 6-311+G(3df) basis set. The equilibrium conformations are characterized by skew structure with dihedral angles COOO and SOOO of about 90º and 95º, respectively. The most stable structures were also calculated using the G3(MP2)B3 and G4(MP2) ab initio methods and with the functional M06-2X/6-311+G(3df). Average standard enthalpies of formation at 298 K derived for FC(O)OOO(O)CF, FS(O2)OOO(O2)SF and FC(O)OOO(O2)SF from isodesmic reactions energies calculated at the G3(MP2)//B3LYP/6-311++G(3df,3pd) and G4(MP2) levels of theory are predicted to be -195.4, -255.6, and -226.5 kcal mol-1. From these values, O-O bond dissociation enthalpies of 25?33 kcal mol-1 were estimated.